EFEKTIVITAS SISKOHAT DALAM PELAYANAN PENDAFTARAN IBADAH HAJI DI KANTOR KEMENTERIAN AGAMA KOTA METRO - Hasrun Afandi Umpu Singa; Muhammad Saleh; Al Fahry Annur (Institut Agama Islam Negeri Metro, 2022)
This study aims to find out the effectiveness of the Integrated Hajj Information and Computerization System (SISKOHAT) in the hajj registration service at the Ministry of Religious Affairs of Metro City because of the increasing number of prospective pilgrims registering for Hajj at the Ministry of Religious Affairs of Metro City, phu section staff feel that the services provided to prospective pilgrims are less than the maximum this is due to the limited number of staff. Therefore, the registration and implementation of hajj is assisted by using various applications, with the core application, namely the Integrated Hajj Information and Computerization System (SISKOHAT) which can facilitate the data collection of prospective hajj pilgrims. This research is a type of field research or field research. The nature of this research is qualitative descriptive. The data collection techniques used are observation, mandalam interviews and documentation. Data analysis is carried out through several stages, namely: data reduction, data display and conclusions. The results showed that the SISKOHAT in the hajj registration service at the Metro City Ministry of Religious Affairs Office has been effective. SISKOHAT is the spearhead of hajj services, because all service processes in Hajj, especially in registration and cancellation, the execution is at SISKOHAT. It cannot be done if there is no SISKOHAT, so SISKOHAT is the key to the services in the Hajj and Umrah Organizing Section.